Dilemma Ekonomi Melayu: Dari Melayu Kopi Daun Hingga Kapitalisme Global - Zed, Mestika (Fakultas Ilmu Sosial Universitas Negeri Padang, 2010)
ABSTRACT This essay is merely an initial notion talking about the possibility of the present and the rise of a movement of the Malay economic organization in the regional level which based on the common history and their cultural traits. The main problems faced by the Malay World are, of course, dilemmatic and complicated as well, not only the existing tension between society and the state on the one side but also between society and the global economic powers on the other. However, the effort toward these movements is possible, even needs to supported, either academically or creativelly. Kata Kunci: Dunia Melayu, Kesadaran Melayu, Ekonomi Melayu, Kapitalisme Global, Minangkabau